Detection and identification of voltage disturbances via clustering and wavelets - Mukerjee R.N.; Tanggawelu B.; Ariffin A.E.; Basha A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Use of consumer devices sensitive to power system disturbances, the increasing awareness of power quality issues and deregulation have created a need for extensive monitoring of the power system operation. In electric power distribution system operation, voltage disturbance is a common phenomenon. A fuzzy diagnostic technique is suggested for detecting the cause of voltage disturbance, so that appropriate remedial procedures could be initiated during system operation. The method uses indices like PN factor, characteristic voltage, zero sequence voltage and also proposes an index termed characteristic frequency, extracted from zero sequence voltage using wavelets. 2002 IEEE.